Marine biofilms on different fouling control coating types reveal differences in microbial community composition and abundance. Issue 4 (24th August 2021) - Papadatou, Maria; Robson, Samuel C.; Dobretsov, Sergey; Watts, Joy E. M.; Longyear, Jennifer; Salta, Maria
Abstract: Marine biofouling imposes serious environmental and economic impacts on marine applications, especially in the shipping industry. To combat biofouling, protective coatings are applied on vessel hulls which are divided into two major groups: biocidal and non‐toxic fouling release. The current study aimed to explore the effect of coating type on microbial biofilm community profiles to better understand the differences between the communities developed on fouling control biocidal antifouling and biocidal‐free coatings. Biocidal (Intersmooth® 7460HS SPC), fouling release (Intersleek® 900), and inert surfaces were deployed in the marine environment for 4 months, and the biofilms that developed on these surfaces were investigated using Illumina NGS sequencing, targeting the prokaryotic 16S rRNA gene. The results confirmed differences in the community profiles between coating types. The biocidal coating supported communities dominated by Alphaproteobacteria ( Loktanella, Sphingorhabdus, Erythrobacter ) and Bacteroidetes ( Gilvibacter ), while other taxa, such as Portibacter and Sva0996 marine group, proliferated on the fouling‐release surface. Knowledge of these marine biofilm components on fouling control coatings will serve as a guide for future investigations of marine microfouling as well as informing the coatings industry of potential microbial targets for robust coating formulations. Abstract : Marine biofilms constitute the pioneering components of biofouling, a phenomenon with significant environmental and economic impacts in maritime applications. Antifouling control strategies are applied on vessel hulls based on the application of protective paints. Here, we explored the in situ prokaryotic biofilm community composition and abundance on different types of commercial fouling control coatings (fouling release, biocidal) employing next‐generation sequencing targeting the 16S rRNA gene. Our results indicated distinct microbial community profiles between coating types, with specific genera contributing to differences between surfaces.